Pulsatile secretion of luteinizing hormone and its relation to pause days and egg production in dual purpose hens treated with antiprolactin agent - Reddy, I.J; Kiran, G.R.; Mondal, S.; Samireddypalle, A. (2009)
Objective of this study is to investigate the amplitude and frequency of luteinizing hormone (LH), in backyard birds treated with antiprolactin agent and its effects on plasma prolactin (PRL), LH, estradiol (E2ß), progesterone (P4), intersequence pause days and egg production. Birds were divided in 2 groups (control and treated) of 12 birds each. Birds in treated group were administered s/c with anti PRL agent (2-bromo-?-ergocriptine) solution containing @100 mg/kg body weight/hen/week (treated group) from 72 to 82 weeks of age. And controls were placebo. Inter sequence days and egg productions were recorded daily from both the groups. Plasma PRL concentration was lower in bromocriptine treated birds with high concentrations of LH, its 3 h LH surges, E2ß and P4 in plasma. Treated birds showed higher egg production, less pause days with concomitant increase in plasma concentration of LH, its amplitude and frequency, besides steroid hormones required for egg formation and oviposition. It is hypothesized that control of PRL secretion with antiprolactin agent, caused enhanced steroid hormone profile; and LH surges required for egg formation and egg lay with lower incidence of pause days in backyard birds enabled the birds to lay more eggs even later in the productive period with under normal husbandry conditions.